2019
DOI: 10.1016/j.celrep.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Human Pluripotent Stem Cell-Derived Tumor Model Uncovers the Embryonic Stem Cell Signature as a Key Driver in Atypical Teratoid/Rhabdoid Tumor

Abstract: Highlights d SMARCB1-deficient human iPSCs give rise to AT/RT-like tumors d ESC-like signature induces rhabdoid histology and causes a poor prognosis d AT/RT exhibits ESC-like transcriptional signature and DNA methylation landscape d ESC-like signature could be a therapeutic target for AT/RT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Their origin from pluripotent progenitors confers a high level of heterogeneity to these tumors, which is often the major hurdle for effective treatment. Recently, it has been demonstrated that by using a human pluripotent stem cell (hPSC)-derived tumor model in various ETs, particularly atypical teratoid/rhabdoid tumors (AT/RT), the presence of an embryonic stem cell (ESC)-like signature is associated with histology and poor prognosis of these tumors (2). These findings suggest that the activation of an early embryonic program in the hPSC progenitors may govern the genetic and epigenetic changes leading to the alteration of the differentiation potential of ETs.…”
Section: Embryonal Tumors and Pluripotent Progenitorsmentioning
confidence: 99%
“…Their origin from pluripotent progenitors confers a high level of heterogeneity to these tumors, which is often the major hurdle for effective treatment. Recently, it has been demonstrated that by using a human pluripotent stem cell (hPSC)-derived tumor model in various ETs, particularly atypical teratoid/rhabdoid tumors (AT/RT), the presence of an embryonic stem cell (ESC)-like signature is associated with histology and poor prognosis of these tumors (2). These findings suggest that the activation of an early embryonic program in the hPSC progenitors may govern the genetic and epigenetic changes leading to the alteration of the differentiation potential of ETs.…”
Section: Embryonal Tumors and Pluripotent Progenitorsmentioning
confidence: 99%
“…In culture conditions inducing neural differentiation, SMARCB1 was shown to be essential for increased chromatin accessibility at neural differentiation genes and silencing of pluripotency-related super-enhancers (Wang et al, 2017;Langer et al, 2019). Furthermore, SMARCB1null iPSCs that were transplanted into mice were able to generate MRT (Terada et al, 2019). Interestingly, iPSCs that had further progressed to neural progenitor cells (NPCs) generated tumors without rhabdoid features.…”
Section: Pluripotent Stem Cell-derived Cell Linesmentioning
confidence: 99%
“…Recently, the organoid technology was also successfully applied to several pediatric cancers, including embryonal tumors such as MRT and Wilms tumors (Schutgens et al, 2019;Calandrini et al, 2020). The efficient establishment and cryopreservation of tumor organoid models from primary patient tissue allows for the generation of large patient cohorts MYCN overexpression in mouse primary NCCs (Olsen et al, 2017) MYCN/ALK-F1174L overexpression in a mouse NC cell-line (Schulte et al, 2013) Mouse-human chimeras with MYCN overexpression in iPSC-derived hNCCs (Cohen et al, 2020) Engineering human 1p36 deletions in mouse NCCs (García-López et al, 2020) Retinoic acid treatment (Lone et al, 2016;Westerlund et al, 2017) HDAC inhibitors (Hahn et al, 2008;Frumm et al, 2013) EZH2 inhibitors (Chen et al, 2018) MRT Neural crest cells (NCCs) SMARCB1 knockout in iPSCs (Terada et al, 2019) SMARCB1 knockdown in ESCs (Langer et al, 2019) SMARCB1 knockout in cerebellar organoids (Parisian et al, 2020) HDAC inhibitors (Muscat et al, 2016) EZH2 inhibitors (Knutson et al, 2013) Medulloblastoma Neural progenitor cells c-MYC overexpression in cerebellar organoids (Ballabio et al, 2020) MYCN overexpression in neuroepithelial stem cells (Huang et al, 2019) Retinoic acid treatment (Patties et al, 2016) EZH2 inhibitors (Cheng et al, 2020) SHH inhibitors (Ocasio et al, 2019) BET-bromodomain inhibitors (Bandopadhayay et al, 2019) DIPG Oligodendrocyte precursor cells H3K27M mutations in hESC derived NPCs (Funato et al, 2014) ACVR1 mutations in neurospheres (Hoeman et al, 2019) HDAC inhibitors (Anastas et al, 2019) BET-bromodomain inhibitors (Mohammad et al, 2017) Retinoblastoma Cone precursor cells RB1 depletion in fetal retinal cell cultures (Xu et al, 2014) RB1 depletion in hESC derived retinal organoids (Liu H. et al, 2020;…”
Section: Reverse Tumor Modeling and Differentiation Therapymentioning
confidence: 99%
“…To overcome the laborious and time-consuming processes of generating GEM models, Zuckermann 41) Huang et al 43) Terada et al 45) Koga et al 47) Feasibility in experimental standardization in isogenic background Enabling human tumor biology investigation…”
Section: Spontaneous Mouse Brain Tumor Models Using Genome Engineeringmentioning
confidence: 99%
“…disrupted SMARCB1 , which is recurrently affected in atypical teratoid rhabdoid tumors (AT/RT), 44) to model this malignant pediatric brain cancer. 45) This study presented a potential use of brain tumor cells derived from genetically engineered human iPSCs for drug screening.…”
Section: Brain Tumor Models Derived From Genome-engineered Human Stemmentioning
confidence: 99%